Morphofunctional Features of Glomeruli and Nephrons After Exposure to Electrons at Different Doses: Oxidative Stress, Inflammation, Apoptosis - Grigory Demyashkin; Sergey Koryakin; Mikhail Parshenkov; Polina Skovorodko; Matvey Vadyukhin; Zhanna Uruskhanova; Yulia Stepanova; Vladimir Shchekin; Artem Mirontsev; Vera Rostovskaya; Sergey Ivanov; Petr Shegay; et al. (Current Issues in Molecular Biology)
Kidney disease has emerged as a significant global health issue, projected to become the fifth-leading cause of years of life lost by 2040. The kidneys, being highly radiosensitive, are vulnerable to damage from various forms of radiation, including gamma (γ) and X-rays. However, the effects of electron radiation on renal tissues remain poorly understood. Given the localized energy deposition of electron beams, this study seeks to investigate the dose-dependent morphological and molecular changes in the kidneys following electron irradiation, aiming to address the gap in knowledge regarding its impact on renal structures. The primary aim of this study is to conduct a detailed morphological and molecular analysis of the kidneys following localized electron irradiation at different doses, to better understand the dose-dependent effects on renal tissue structure and function in an experimental model. Male Wistar rats (n = 75) were divided into five groups, including a control group and four experimental groups receiving 2, 4, 6, or 8 Gray (Gy) of localized electron irradiation to the kidneys. Biochemical markers of inflammation (interleukin-1 beta [IL-1β], interleukin-6 [IL-6], interleukin-10 [IL-10], tumor necrosis factor-alpha [TNF-α]) and oxidative stress (malondialdehyde [MDA], superoxide dismutase [SOD], glutathione [GSH]) were measured, and morphological changes were assessed using histological and immunohistochemical techniques (TUNEL assay, caspase-3). The study revealed a significant dose-dependent increase in oxidative stress, inflammation, and renal tissue damage. Higher doses of irradiation resulted in increased apoptosis, early stages of fibrosis (at high doses), and morphological changes in renal tissue. This study highlights the dose-dependent effects of electrons on renal structures, emphasizing the need for careful consideration of the dosage in clinical use to minimize adverse effects on renal function.